Effect of manganese content on microstructure and properties of welded joints of U71Mn rails - Wang, Chenyang (Frontiers in Materials, 2025)
Manganese (Mn) makes important role in the microstructure and mechanical properties of flash welded joints of the commonly applied U71 Mn rail. In this work, two rail steels with different Mn concentration are tested: U71Mn (Mn of 1.03 wt%) and modified U71Mn steel (Mn of 0.94 wt%). Grey spots, micro cracks, and martensitic transformation in the welded joints are characterized by scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and high-speed photography. It is discovered that the decrease of the manganese content enhances the quality of the weld joint. 65% increase in impact toughness can be achieved, while the length of network ferrite in the web region reduced from 1.0 mm to 0.3 mm. Quantitative metallography indicates that the carbon equivalent of the weld metal, not its manganese content, exercises more control over the martensitic transformation with a 66% correlation coefficient. The study also shows that the average grey spot created in the weld metal has about 77% manganese segregation. Fatigue tests of welded joints show that micro cracks are formed due to the larger size of the MnS inclusions but the effect on joint integrity can be minimized through control of composition. The conclusions reached here touch on critical aspects necessary for the development of rail steels possessing greater serviceability and weldability, paving the way toward the implementation of high-speed railway systems.